Teachers’ Perceived Impacts of Finger-Counting Manipulative as Basis for a Solid Foundation in Mathematics in Nigeria - AKINBOBOYE, J.T.; AKANDE, J.A.; COBBINAH, Andrews; OYELADE, E.; OGIDIS, E. (Journal of Research in Educational Sciences; Vol 14 No 16 (2023): JRES, Volume XIV, Issue 16, Winter 2023DO - 10.14505/jres.v14.16.02, 2023)
This paper was designed to determine preschool, primary school teachers, and secondary school Mathematics teachers’ and special educators’ views of finger-counting as the basis for a solid foundation in learning Mathematics. One hundred Participants were selected using purposive sampling. One research question and three hypotheses were raised to guide the study. The adapted instrument from Mutlu et al. (2020) titled the finger-counting questionnaire with a reliability index of 0.78 was used to gather data for the study. Data collected were analyzed using percentage, mean, t-test, and ANOVA statistics. The results showed that teachers perceived impacts of finger-counting that; it facilitates learning by touching, turns abstract into concrete resulting in meaningful learning, makes counting practical and accessible, facilitates retention and internalization, increases numerical, arithmetic, and problem-solving skills, and also improves attitudes towards mathematics. Findings also revealed no differences exist among teachers on the perceived impact of finger-counting as the basis for a solid foundation in learning Mathematics based on their gender and teachers’ category but significant differences exist in their years of teaching experience. In conclusion, finger counting should not be seen as an alternative or optional but as an indispensable tool in teaching and learning Mathematics. The researchers recommended that because people abandon finger-counting strategies once they develop cognitive and affective skills, finger-counting should be seen as a transition process rather than an obstacle to the development of mental arithmetic skills.